IDENTIFIKASI KESULITAN BELAJAR DAN LANGKAH-LANGKAH PERBAIKANNYA PADA MATA PELAJARAN IPS SISWA KELAS V GUGUS I KECAMATAN LINGSAR - Ningrum, Sofiany Nawang; Nurhasanah, Nurhasanah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2018)
This research have purpose to identification the difficulties that students have experience, to know the factors which cause the difficulties, and to know the improvement steps that teacher have done to influenced five grade student gugus I in Lingsar subdistric. This research is descriptive research with qualitative approachment. The subject in this research are students in the five grade gugus I in Lingsar subdistric, which got difficulties experience at social studies subject, and teacher class.Aggregation data technical use interview technical, observation, and documentation. The data analysis of this research use Interactive Analysis Method. To have data validity, the research to do credibility test,transferability, dependability and confirmability. Research product of the study indicate that the difficulties experienced by student social studies learning are difficulty in language, difficulity in understanding the concept, difficulity in remembering and mistake because of carelessness.The factors that affect learning difficulties is internal factors, that are low shrewdness, attitude less attention to learning, low learning interest, and low learning motivation. While, external factors that are, lack of parents attention, the ambience of learning at home is less condusive, circle condition, influence of mass media, the presentation of learning materials is less interesting, learning methods are less varied, rarely used instructional media, and means of learning is not complete yet. Improvement steps that have been done by classroom teacher are give special attention to students who have learning difficulties, teacher try to get closer to students, the teacher explains the material that is not yet understood and teacher also do remedial activities.